The Identification of Beliefs From Asset Demand - Kübler, Felix; Polemarchakis, Herakles (Econometrica, 2017)
The demand for assets as prices and initial wealth vary identifies beliefs and attitudes towards risk. We derive conditions that guarantee identification with no knowledge either of the cardinal utility index or of the distribution of future endowments or payoffs of assets; the argument applies even if the asset market is incomplete and demand is observed only locally.